2018
DOI: 10.18332/tid/84118
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for use, potential use, or discontinued use of hookah among us young adult college students

Abstract: Innovations in media educational campaigns and health warning labels on cigarettes and other tobacco productsFO-329-3 Over-time changes in reactions to pictorial health warning labels and association with quitting behavior among adult smokers in Thailand: findings from ITC Thailand survey (2005 -2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the US, a survey conducted in 2014 and 2015 showed that college students are more likely to start WTS, and misperception of the harm of WTS was found especially in young population and never smokers [6]. Studies have shown that flavors are one of the major reasons for young people to smoke waterpipe tobaccos [7,8], and social influence is the other one [9]. The fruit flavor is the preferred flavor among waterpipe tobacco users, and females are found to be more inclined to consume flavored waterpipe products than males [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the US, a survey conducted in 2014 and 2015 showed that college students are more likely to start WTS, and misperception of the harm of WTS was found especially in young population and never smokers [6]. Studies have shown that flavors are one of the major reasons for young people to smoke waterpipe tobaccos [7,8], and social influence is the other one [9]. The fruit flavor is the preferred flavor among waterpipe tobacco users, and females are found to be more inclined to consume flavored waterpipe products than males [10].…”
Section: Introductionmentioning
confidence: 99%